AGTR2 and sprint/power performance: a case-control replication study for rs11091046 polymorphism in two ethnicities - Yvert, Thomas P.; Zempo, Hirofumi; Gabdrakhmanova, Leysan J.; Kikuchi, Naoki; Miyamoto-Mikami, Eri; Murakami, Haruka; Naito, Hisashi; Cieszczyk, Pawel; Leznicka, Katarzyna; Kostryukova, Elena S.; Alexeev, Dmitry G.; Egorova, Emiliya S.; et al. (Biology of Sport, 2018)
We aimed to replicate, in a specific athletic event cohort (only track and field) and in two different ethnicities (Japanese and East European, i.e. Russian and Polish), original findings showing the association of the angiotensin-II receptor type-2 gene (AGTR2) rs11091046 A>C polymorphism with athlete status. We compared genotypic frequencies of the AGTR2 rs11091046 polymorphism among 282 track and field sprint/power athletes (200 men and 82 women), including several national record holders and Olympic medallists (214 Japanese, 68 Russian and Polish), and 2024 control subjects (842 men and 1182 women) (804 Japanese, 1220 Russian and Polish). In men, a meta-analysis from the two combined cohorts showed a significantly higher frequency of the C allele in athletes than in controls (odds ratio: 1.62, P=0.008, heterogeneity index I 2=0%). With regard to respective cohorts, C allele frequency was higher in Japanese male athletes than in controls (67.7% vs. 55.9%, P=0.022), but not in Russian/Polish male athletes (61.9% vs. 51.0%, P=0.172). In women, no significant results were obtained by meta-analysis for the two cohorts combination (P=0.850). The AC genotype frequency was significantly higher in Russian/Polish women athletes than in controls (69.2% vs. 42.1%, P=0.022), but not in Japanese women athletes (P=0.226). Our results, in contrast to previous findings, suggested by meta-analysis that the C allele of the AGTR2 rs11091046 polymorphism is associated with sprint/power track and field athlete status in men, but not in women.